Genomic epidemiology of vancomycin-resistant enterococcus faecium (VREfm) in Latin America: revisiting the global VRE population structure (2020)
Little is known about the population structure of vancomycin-resistant Enterococcus faecium (VREfm) in Latin America (LATAM). Here, we provide a complete genomic characterization of 55 representative Latin American VREfm recovered from 1998–2015 in 5 countries. The LATAM VREfm population is structured into two main clinical clades without geographical clustering. Using the LATAM genomes, we reconstructed the global population of VREfm by including 285 genomes from 36 countries spanning from 1946 to 2017. In contrast to previous studies, our results show an early branching of animal related isolates and a further split of clinical isolates into two sub-clades within clade A. The overall phylogenomic structure of clade A was highly dependent on recombination (54% of the genome) and the split between clades A and B was estimated to have occurred more than 2,765 years ago. Furthermore, our molecular clock calculations suggest the branching of animal isolates and clinical clades occurred ~502 years ago whereas the split within the clinical clade occurred ~302 years ago (previous studies showed a more recent split between clinical an animal branches around ~74 years ago). By including isolates from Latin America, we present novel insights into the population structure of VREfm and revisit the evolution of these pathogens.